A identidade cultural e a educação - Pastori, Fernanda [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The culture is embedded in all social and especially those aimed at the formation of the citizen as a whole. So the school is a major means of training and is not neutral on the influence of culture on student learning. The social milieu in which it is inserted or not contributing to great learning and shapes the human being as the pre-existing norms in society. Link education with the culture of the student from considering it as a whole helps to understand how this builds your knowledge and see how the world around them. The production of new knowledge through what we see is also part of the cultural and social practices. In a society where looks are extremely exploited and relate it to the formation of knowledge through social helps in understanding the culture as a learning process and identify the individual as having a cultural identity with social significance. This research addresses how school culture has treated the various existing and possible means of study such as art, treatment of the curriculum and within the classroom, emphasizing its importance in the educational context

A cultura está inserida em todos os meios sociais e principalmente naqueles que visam a formação do cidadão em seu todo. Sendo assim, a escola é um dos principais meios de formação e não está neutra em relação à influência da cultura na aprendizagem dos alunos. O meio social, em que o aluno está inserido, contribui, ou não, para a aprendizagem e molda o ser humano conforme as normas já pré-existentes na sociedade. Relacionar a educação com a cultura proveniente do educando, analisando-o como um todo, auxilia a entender a maneira como ele constrói seu conhecimento e como vê o mundo ao seu redor. A produção de novos saberes através do que se vê, também faz parte das práticas culturais e sociais. Em uma sociedade onde o visual é extremamente explorado, relacioná-lo com a formação do conhecimento, através do social, auxilia na compreensão da cultura como um processo de aprendizagem e a identificar o indivíduo como possuidor de uma identidade cultural com importância social. Esta pesquisa aborda como a escola tem tratado a cultura pelos diversos meios existentes e possíveis de estudo como arte, tratamento do currículo e dentro da própria sala de aula, ressaltando sua importância no contexto educacional
Keywords: Cultura; Educação; Aprendizagem; Prática política; Culture; Education; Political practice; Learning